Penggunaan bahasa isyarat dalam pembelajaran seni tari bagi siswa tunarungu tingkat sekolah menengah pertama di sekolah luar biasa - Sri Murwati; Syefriani Syefriani (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2024)
This study aims to describe the use of sign language in dance learning in deaf students at the junior high school level at SLB Negeri Siak. This study uses a descriptive qualitative method. The data collection techniques used are observation, interviews and documentation. The results showed that the use of sign language in dance learning for deaf students at the junior high school level at SLB is very effective in improving their understanding and skills. Teaching methods that use SIBI and BISINDO sign language help deaf students to more easily understand dance movement instructions. . The findings make an important contribution to the development of more inclusive and effective teaching methods in SLB, as well as providing practical guidance for teachers in teaching dance to deaf students.